2014
DOI: 10.1111/cge.12363
|View full text |Cite
|
Sign up to set email alerts
|

Novel KDM6A (UTX) mutations and a clinical and molecular review of the X‐linked Kabuki syndrome (KS2)

Abstract: We describe seven patients with KDM6A (located on Xp11.3 and encodes UTX) mutations, a rare cause of Kabuki syndrome (KS2, MIM 300867) and report, for the first time, germ-line missense and splice-site mutations in the gene. We demonstrate that less than 5% cases of Kabuki syndrome are due to KDM6A mutations. Our work shows that similar to the commoner Type 1 Kabuki syndrome (KS1, MIM 147920) caused by KMT2D (previously called MLL2) mutations, KS2 patients are characterized by hypotonia and feeding difficultie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(150 citation statements)
references
References 18 publications
6
137
2
5
Order By: Relevance
“…KDM6A is a lysine specific histone demethylase that controls tissue-specific expression of genes involved in development as well as the cell cycle [3438]. Loss of function mutations of KDM6A which cause Kabuki Syndrome Type 2, KS2, are most often somatic mutations [18, 20, 2225, 27]. Arnoux, et al, reported that hypoglycemia occurs in 11% of Kabuki Syndrome patients overall [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KDM6A is a lysine specific histone demethylase that controls tissue-specific expression of genes involved in development as well as the cell cycle [3438]. Loss of function mutations of KDM6A which cause Kabuki Syndrome Type 2, KS2, are most often somatic mutations [18, 20, 2225, 27]. Arnoux, et al, reported that hypoglycemia occurs in 11% of Kabuki Syndrome patients overall [39].…”
Section: Discussionmentioning
confidence: 99%
“…Arnoux, et al, reported that hypoglycemia occurs in 11% of Kabuki Syndrome patients overall [39]. Recent reports suggest that hypoglycemia may occur in a much higher proportion of patients with KS2 associated with KDM6A mutations [13, 20, 22, 26]. The mechanism by which haploinsufficiency for KDM6A causes hyperinsulinism in Kabuki Syndrome is not known, but has been suggested to involve disruption of epigenetic changes during pancreatic differentiation [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…() who reported mutations in KMT2D (MIM#602113) as the major genetic cause of the disorder. More recently, deletions or mutations of KDM6A (MIM#300128) have been reported to underlie a small proportion of affected individuals (Banka et al., ; Bögershausen, Bruford, & Wollnik, ; Lederer et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A small number of patients have also been reported in whom Kabuki syndrome is attributed to mosaic small or whole KMT2D gene deletions, or intragenic multi-exon duplication (Banka et al, 2013). Causative missense and splice-site mutations in, and deletions involving, the KDM6A (lysine-specific demethylase 6A) gene, located at Xp11.3, have been infrequently reported (Lederer et al, 2012;Miyake et al, 2013;Cheon et al, 2014;Banka et al, 2015). KMT2D and KDM6A are trithorax proteins which interact to modulate histone lysine methylation, thereby epigenetically regulating gene expression (Kim et al, 2014;Adam, 2015).…”
Section: Introductionmentioning
confidence: 99%